Use of GLP-1 receptor agonist and risk of osteoporosis among patients with type 2 diabetes: a real-world study - Ming Chen; Yiming Lyu; Jingwei Zhao; Xianwei Han; Tao Huang; Tongtao Yang; Yong Zhou (Frontiers in Endocrinology)
BackgroundType 2 diabetes mellitus (T2DM) is an independent risk factor for osteoporosis, increasing the risk of fractures and poor prognosis. Recent studies suggest that glucagon-like peptide-1 receptor agonists (GLP-1 RAs) may play a protective role in bone metabolism. However, limited evidence exists on their effect on osteoporosis incidence in T2DM patients. This study aimed to evaluate the association between GLP-1 RA use and osteoporosis risk in a real-world cohort of elderly T2DM patients.MethodsThis retrospective cohort study utilized electronic medical records (EMRs) from Tangdu Hospital, Xi’an, China, between January 1, 2012, and December 31, 2023. Patients with T2DM who had at least two clinical visits annually and no prior osteoporosis diagnosis (ICD-10: M80-M82) at baseline were included. The primary outcome was the incidence of osteoporosis during follow-up. Cox proportional hazards models were used to evaluate the association between GLP-1 RA use and osteoporosis risk, adjusting for age, sex, BMI, blood pressure, lipid profile, renal function, osteocalcin, vitamin D levels, HbA1c, statin use, antihypertensive medication use, and smoking status. Subgroup analyses were conducted to assess potential effect modifications.ResultsA total of 1,845 patients with T2DM were included, of whom 676 (36.6%) developed osteoporosis during follow-up. Among the 256 patients who received GLP-1 RAs, the incidence of osteoporosis was significantly lower than in those who did not receive GLP-1 RAs (P < 0.01). In the fully adjusted Cox model, GLP-1 RA use was associated with a significantly reduced risk of osteoporosis compared to non-users (hazard ratio [HR] = 0.69, 95% confidence interval [CI] =0.45-0.84, P < 0.05). Subgroup analyses indicated that the protective effect of GLP-1 RAs was consistent across age, sex, BMI, smoking status, and antihypertensive medication use (P for interaction > 0.05).ConclusionIn patients with T2DM, patients with treatment of GLP-1 RAs resulted in lower risks of osteoporosis than those without treatment of GLP-1 RAs. These findings support the potential bone-protective effects of GLP-1 RAs but further randomized controlled trials (RCTs) or large-scale database analyses are needed to confirm these observations and guide clinical recommendations.